The Idea of Education: Development or Service Delivery? - V. E. Ljovkin; A. O. Ljovkina; E. L. Docenko; L. M. Volosnikova (Образование и наука)
Introduction. In recent years, the debates over the education crisis, its essence and the role in the development of a person and culture in general have underlined the need to scientifically define the concept of modern education. The present article is debatable and theoretical; therefore, it explores the idea of education from the perspective of the current trend – the classification of education as a service sector.The aim of the article is to scientifically justify irrelevance of the ideas of education as a “commercial service” through the discussion of consequences of such an interpretation.Methodology and research methods. The research methodology is based on a meta-systemic approach, which allows us to consider education as the system in a number of other social institutes and structures and as an element of a larger system. The logical-semantic analysis, hermeneutic method and synthesis of the views among the representatives in the filed of the humanities were used to study the phenomenon of “educational services”. To determine own position, the authors of the present article used the procedure of separating “social construction paradigms” (as a set of principles of knowledge and transformation of social reality), which make it possible to give diverse definitions of society and to introduce the concepts of the essence and the role of education.Results. The concept of “educational services” is analysed as a speech template, a way of thinking, a legal concept, a call to changing social practice and a probable project. The authors reveal a conceptual, semantic substitution, which negatively affects the result of the educational process: the meaning of profit has taken the place of the sense of personal development and social long-term viability and development of society. It is demonstrated that this semantic substitution is a natural consequence of the market laws, going beyond the social control, in particular, their semi-legitimate expansion into the sphere of education, which is a significant public good.Scientific novelty. It is proved that an established expression “educational services” in modern discourse contributes to destructive transformations of the citizens’ mentality and social space. The concepts of “service” and “education” are characterised according to a set of the following criteria: a subject of activity, its nature, a recipient role, specificity of the methods of activity, its result (or its goal) and quality assessment. It is concluded that the sectors of service and education can be characterised as joint constructive human activities, but they are fundamentally different activities.Practical significance. The obtained results could be applied to provide purposeful adjustment processes for conceptual management of the education sector.